Optimized preparation of zinc-inorganic antibacterial material containing samarium using response surface methodology - 毛翠萍 张彬 唐晓宁 李欢 何琼 (Journal of rare earths, 2014)
A Box-Behnken design （BBD） of response surface methodology （RSM） was used to optimize the preparation of the Zn-Sm antibacterial white carbon black by the sol-gel method. The statistical analysis of the results showed that the particle size of the Zn-Sm antibacterial white carbon black was significantly affected by the reaction time, reaction temperature and the stirring speed. According to analysis of variance （ANOVA）, the values of the determination coefficient （R2=0.9821） and the ＂Pred R-Squared＂ of 0.8227 were in reasonable agreement with the ＂Adj R-Squared＂ of 0.9591. It was indicated that this model could be used to navigate the design space. The optimized reaction time, temperature and the stirring speed were 0.88 h, 87.83 ℃, and 473.45 r/rain, respectively. In addition, the bacteriostasis rate of the product was about 97.92%.